Using Translanguaging to Decolonize English Language Teaching in Colombia: A Narrative Inquiry - Ubaque-Casallas, Diego F. (Íkala, Revista de Lenguaje y Cultura, 2023)
Today’s classrooms are linguistically diverse. Nonetheless, English language teaching still uses a separatist model in which other languages and identities are reduced and subalternized. This evident separation of languages has forced many English speakers to identify with the non-native label, prevented them from using the linguistic resources they have previously acquired from other languages to communicate and learn in given settings, and made the different ways they exist invisible. From a narrative perspective, this article documents how two English teacher educators do not conform to this native ideology by resorting to a translanguaging pedagogy. It narrates their pedagogical experiences and insights preparing English teachers in Colombia and explores how they use their linguistic repertoire as a mechanism to teach. Their narratives reveal that translanguaging is a pedagogy that allows English teachers to challenge discourses framed in monolingual perspectives. They also indicate that by implementing a translanguaging pedagogy, English teachers can foster and enact a counter-nonnative ideology that enables them to reclaim their identities. All in all, the results of this inquiry suggest that it is worth pursuing translanguaging as a language pedagogy that disrupts colonial language practices and identity discourses.